New morphological and molecular data on Lecithocladium excisum (Rudolphi, 1819) Lühe, 1901 (Digenea: Hemiuridae) from brazil: SEM analysis, new host record, and synonymy with Lecithocladium chaetodipteri. - Machado, Arthur Bessi (2025)
This study aims to enhance the understanding of the parasitic digenean species Lecithocladium excisum (Rudolphi, 1819) Lühe, 1901 from Chaetodipterus faber (Broussonet, 1782) (Acanthuriformes: Ephippidae) in Brazil, through scanning electron microscopy and molecular analyses. For scanning electron microscopy, collected specimens were dehydrated through a graded ethanol series, critical point dried with carbon dioxide, and coated with gold. DNA was extracted and amplified using the partial 28S rDNA primer pair D1–D3 and the mitochondrial primer pair JB3 and CO1-R trema. Phylogenetic analyses were performed using maximum likelihood and Bayesian inference methods. Observations from scanning electron microscopy corroborated those described in stained whole mounts in previous literature, in addition to revealing novel morphological features. Molecular and phylogenetic analyses demonstrated and supported that Lecithocladium chaetodipteri Amato, 1983 is a synonym of L. excisum. The analysis of morphometric data available in the literature further corroborates this finding. Additionally, this study reports a new host record for L. excisum.